contestada

IMPORTANT, PLEASE HELP QUICKLY! 15 POINTS
Explain how to factor the expression q(x)=9x2−24x+16 to the expression q(x)=(3x−4)2 . You may show your work. Be sure to include a detailed explanation of your steps.

Respuesta :

Answer:

Given function:

[tex]q(x)=9x^2-24x+16[/tex]

To factor a quadratic in the form [tex]ax^2+bx+c[/tex],  find two numbers that multiply to [tex]ac[/tex] and sum to [tex]b[/tex]:

[tex]ac=9 \cdot 16=144[/tex]

Two numbers that multiply to 144 and sum to -24 are: -12 and -12

Rewrite [tex]b[/tex] as the sum of these two numbers:

[tex]\implies q(x)=9x^2-12x-12x+16[/tex]

Factorize the first two terms and the last two terms separately:

[tex]\implies q(x)=3x(3x-4)-4(3x-4)[/tex]

Factor out the common term [tex](3x-4)[/tex]:

[tex]\implies q(x)=(3x-4)(3x-4)[/tex]

Therefore:

[tex]\implies q(x)=(3x-4)^2[/tex]

ACCESS MORE